La nouvelle Afrique du Sud à la plage ! Usages et fréquentation de trois plages de la péninsule du Cap - Hélène Frogneux (EchoGéo)
According to all, Cape Town is the most European of South-African cities. Due to its coastal situation Cape Town is both a major port and an appreciated seaside destination, both by the South-Africans and by the foreign tourists. As was every public space, beaches were segregated under apartheid. Nowadays they are theoretically open to everyone, without distinction of race. But there is a gap between institutional desegregation and the desegregation de facto. Capetonian beaches reflect the mutations and the changes going on at the dawn of the 2010 World Cup.